2007
DOI: 10.1007/s10571-006-9122-0
|View full text |Cite
|
Sign up to set email alerts
|

Chelating Compound, Chrysoidine, Is More Effective in Both Antiprion Activity and Brain Endothelial Permeability Than Quinacrine

Abstract: 1. As an extension of our previous study of quinacrine and its derivatives, chelating chemicals were screened to obtain more effective, better brain-permeable antiprion compounds using either prion-infected neuroblastoma cells or brain capillary endothelial cells.2. Eleven chemicals were found to have antiprion activity. Most of them shared a common structure consisting of benzene or naphthalene at either end of an azo bond. Structure-activity data suggest that chelating activity is not necessary but might con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 19 publications
1
13
0
Order By: Relevance
“…First, the effects of "antiprion" compounds are clearly species/strain-dependent, in that drugs found to restrain prions in one situation may improve replicative ability in another. Based on initial reports of quinacrine's effects on mouse prion propagation in cell culture, a plethora of studies were designed to discern the mechanism of its presumed antiprion effects (19,20,(29)(30)(31)(38)(39)(40)(41)(42)(43)(44)(45), to assess its pharmacokinetics (21,36,42,46) and to derive similar compounds with improved antiprion efficacy (18,20,(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59). These studies continue to this day, despite multiple failed clinical studies in patients with human prion diseases (10)(11)(12)(13)(14)(15).…”
Section: Discussionmentioning
confidence: 99%
“…First, the effects of "antiprion" compounds are clearly species/strain-dependent, in that drugs found to restrain prions in one situation may improve replicative ability in another. Based on initial reports of quinacrine's effects on mouse prion propagation in cell culture, a plethora of studies were designed to discern the mechanism of its presumed antiprion effects (19,20,(29)(30)(31)(38)(39)(40)(41)(42)(43)(44)(45), to assess its pharmacokinetics (21,36,42,46) and to derive similar compounds with improved antiprion efficacy (18,20,(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59). These studies continue to this day, despite multiple failed clinical studies in patients with human prion diseases (10)(11)(12)(13)(14)(15).…”
Section: Discussionmentioning
confidence: 99%
“…Among these models, prion-infected cell models have been the most frequently used since Congo red and polyanionic glycans were found to possess antiprion activity (Caughey and Race 1992;Caughey and Raymond 1993). In fact, our research group has identified dozens of antiprion compounds, including quinacrine and compB, using prion-infected cell models (Doh-ura et al 2000(Doh-ura et al , 2007bIshikawa et al 2004Ishikawa et al , 2006Murakami-Kubo et al 2004;Kawatake et al 2006;Kawasaki et al 2007;Nguyen et al 2008Nguyen et al , 2011Hamanaka et al 2011Hamanaka et al , 2015Teruya and Doh-ura 2013;Nishizawa et al 2014). However, these cell models are not fully compatible with in vivo prion-infected neuronal cells.…”
Section: A Combination Of Multiple Targetsmentioning
confidence: 99%
“…Chrysoidine is a chelating agent with antiprion activity and an ability to easily cross the BBB. However, there is as yet no investigation into the drug's effect on human patients, and has been (inconclusively) associated with cancer [108]. Quinacrine Fig.…”
Section: ) Metal Chelators That Sequester Metalsmentioning
confidence: 99%
“…The structure of quinacrine would suggest that it should act as a chelating agent; however it is likely that the drug has a different mode of action that doesn't rely exclusively on its chelating ability. Administration of the drug does not alter the amounts of PrP C or modify PrP Sc , so the mechanism of the drug is still unknown [108]. Interestingly, although clioquinol and related compounds are effective in assisting in the reduction of A in AD, it was not shown to have an effect against PrP Sc accumulation [109].…”
Section: ) Metal Chelators That Sequester Metalsmentioning
confidence: 99%